2018
DOI: 10.1186/s12936-018-2458-3
|View full text |Cite
|
Sign up to set email alerts
|

Wall-type and indoor residual spraying application quality affect the residual efficacy of indoor residual spray against wild malaria vector in southwest Ethiopia

Abstract: BackgroundResidual efficacy of indoor residual spray may vary with different spray quality and wall surfaces types. This study evaluated the impact of spray quality and wall surface types on residual efficacy of propoxur against wild Anopheles gambiae sensu lato (s.l.) in southwest Ethiopia.MethodsThirty houses of different mud wall surfaces (10 smooth, 10 rough, 10 painted) were selected and randomly allocated into routine and standard spray. The routine spray was conducted by district health office as usual,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
(12 reference statements)
2
19
0
Order By: Relevance
“…This finding is supported by Rohani et al, [4] who stated that efficacy of deltamethrin can be varied depending on the concentration used, formulation, surface of the area, humidity, temperature, and method of evaluation. Significant variation in residual efficacy between different types of wall surfaces was also reported by Desalegn et al, [10] using propoxur and Mutagahywa et al [11] using lambda-cyhalothrin who observed significant differences in mortality rate of An. gambiae exposed to different wall surface types sprayed with the same insecticide.…”
Section: Bio Efficacy Of the Insecticidesupporting
confidence: 62%
See 1 more Smart Citation
“…This finding is supported by Rohani et al, [4] who stated that efficacy of deltamethrin can be varied depending on the concentration used, formulation, surface of the area, humidity, temperature, and method of evaluation. Significant variation in residual efficacy between different types of wall surfaces was also reported by Desalegn et al, [10] using propoxur and Mutagahywa et al [11] using lambda-cyhalothrin who observed significant differences in mortality rate of An. gambiae exposed to different wall surface types sprayed with the same insecticide.…”
Section: Bio Efficacy Of the Insecticidesupporting
confidence: 62%
“…Briefly, the DNA was first extracted using the DNeasyR Blood & Tissue Kit (Qiagen, Valencia, CA). Mosquitoes were then undergoing the detection of malaria parasite using semi-nested and nested PCR techniques followed by sequencing analysis of the small-subunit (SSU) rRNA gene [9] .…”
Section: Adult Survey and Parasite Identificationmentioning
confidence: 99%
“…Residual efficacy differed slightly between type of wall surface. This has been shown for SumiShield TM 50WG and other IRS products before, but the direction of effect is not always consistent [17][18][19]. A multi-country study conducted by Oxborough and colleagues across west and east Africa assessing the residual effect of different IRS products on different wall surfaces showed that residual efficacy of each IRS product was affected by the type of surface and that variations in retention of the active ingredient can differ from country to country, even on similar surfaces [43].…”
Section: Discussionmentioning
confidence: 95%
“…As part of routine monitoring and evaluation (M&E) operations, the residual efficacy of SumiShield TM 50WG was evaluated during the 2018-2019 malaria season. Two different -but common-wall surface (cement and mudplastered) were evaluated, as type of surface is known to affect the residual efficacy of a variety of IRS products [17][18][19]. Apart from testing young (2-5 day old) mosquitoes, which is the current recommendation of WHO, older mosquitoes were exposed as well, and mortality post-exposure tracked for up to 5 days.…”
Section: Introductionmentioning
confidence: 99%
“…It may not also be efficient to spray all housing structures with residual insecticides as it has been shown to work better on painted walls compared to rough walls. 28 ITNs, on the other hand, have been shown to have little or no effect on malaria prevalence, particularly in low malaria epidemiological settings. 29 But other interventions such as MDA and community case management are effective in low endemicity settings.…”
Section: Discussionmentioning
confidence: 99%